Dual Energy Computed Tomography and Effect on the Management of Uric Acid Renal Calculi - AJ Jahangiri; AM Moghaddam (Journal of Radiation and Nuclear Medicine, 2023)
Attenuation differences from 2 x-ray sources allow differentiation and characterization of stone types with similar radiation dose compared to single-energy CT scan. The difference is shown in colours, allowing preoperative prediction and management of stones. We determined the effect of DECT-KUB on urological management of patients with uric acid stones since it was first introduced in our centre. 50 patients with uric acid stones were selected from 2 year groups, each with 25 patients and their urological managements were reviewed retrospectively. We concluded that DECT-KUB is an accurate way of determining the chemical characteristics of renal calculi and can alter patients’ management. It has gained wide acceptance among clinicians in our centre and is now widely used to plan urological management of patients with renal calculi. Based on urological management comparison of patients who presented in the year 2011 with uric acid stones and patients in the year 2020, we concluded that patients with uric acid stones based on DECT-KUB findings can start dissolution therapy instead of surgical extraction or lithotripsy prior to biochemical analysis results become available. Although utility of DECT-KUB is widely accepted among clinicians in our centre it may not be available worldwide and this is the limiting factor in its universal use.
Keywords: OHIP-14